In Doig People's Ears: Portrait of a Changing Community in Sound - Ridington, Robin (Anthropologica, 2022)
Fieldwork among the Beaver Indians of British Columbia, Canada over a period of twenty years has produced an archive of audio tapes documenting the process of transition from a life based on hunting and trapping to one which is integrated into the modern industrial economy. This paper describes techniques for using aural actualities to create audio documentary programs that illustrate these changes. It compares the symbol systems of hunting and gathering people with those of people in contemporary cultures, and suggests that we may learn valuable lessons from the available information about hunters and gatherers.